Penguatan Inovasi Pembelajaran PAI Berbasis Deep Learning: Penelitian Tindakan Sekolah di SMA UII Yogyakarta - Aswal Askah; Ngatiyatul Wafiyah; Riana Agus Tantri (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study aims to strengthen innovation in Islamic Religious Education (PAI) learning through the implementation of a deep learning approach at SMA UII Yogyakarta. The background of this study stems from the lack of variety in PAI learning strategies, which tend to be conventional, thus failing to encourage active student engagement and in-depth understanding. Design/methods – Using a School Action Research (PTS) design, this study involved PAI teachers as key partners in designing, implementing, reflecting on, and improving deep learning-based learning practices. Data were collected through observations, interviews, teacher reflective notes, and documentation over a one month period. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Findings – The results of the study indicate that the implementation of a deep learning approach can improve the quality of PAI learning innovations, particularly in aspects of active student participation, conceptual understanding, and the ability to relate religious values ​​to real life. Teachers act as reflective facilitators who continuously evaluate and improve learning strategies through a cycle of action. This study recommends the development of ongoing training for teachers to strengthen their ability to effectively implement deep learning-based learning in schools.